“Trapped in their Shame”: A Qualitative Investigation of Moral Injury in Forensic Psychiatry Patients - Roth, Sophia L. (Criminal justice and behavior, 2022)
Individuals who engage in criminal behavior for which they are found not criminally responsible (NCR) may be at increased vulnerability to experience moral pain and, in extreme circumstances, moral injury after regaining insight into the consequences of their behavior. Yet, almost no research exists characterizing the nature, severity, or impact of moral pain in this population. Semi-structured interviews were conducted with nine forensic psychiatric patients and 21 of their care providers. Narratives were explored using thematic analysis. Findings demonstrate that NCR patients endorse symptoms consistent with moral injury, including feelings of guilt toward victims, shame for one’s behavior, and a loss of trust in one’s morality. Moral pain is a strong driver of behavior and must be understood as part of a constellation of factors influencing criminality, risk, and recovery. Future research must develop adequate tools to measure and characterize offense-related moral injury to understand its impact on this population.